The Subject of Holodomor in the Ukrainian Artistic Space: Historical Projections of the Art of Contemporary Composers - Vasylenko, Olha; Mudretska, Lilіia; Okner, Irene (Muzikološki zbornik, 2021)
The Great Famine (Holodomor) is man-made famine that convulsed the Soviet republic of Ukraine in the 1930s. Since 2006, the Holodomor has been recognized as a genocide of the Ukrainian people carried out by the Soviet government. The article aims to highlight specific historical, cultural and social conditions that contributed to the dynamics of the Holodomor theme in music. It focuses especially on the musical compositions of this historical tragedy performed at the Kyiv Music Fest Competition. We can observe the linguistic and musical semantics of the opus of tragic imagery, along with the ethnic motifs of the Ukrainian cultural space, including musical rhetorical figures of the Baroque period, Christian symbolism of suffering and salvation, infernal stylistics.